2023
DOI: 10.21203/rs.3.rs-2541636/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors associated with risk sexual behaviors among sexually active college students in Sichuan, China: a cross- sectional survey

Abstract: Background Males account for a significant share of new infections among young people in China. This study aimed to identify the factors associated with risk sexual behaviours, and provide evidence of leverage for effective interventions among male college students. Methods The cross-sectional study was conducted from December 2020 to December 2021 in 16 colleges, located in Sichuan Province, one of the high-risk areas in China. Overall 1640 male college students who reported sexually experienced were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
0
0
Order By: Relevance
“…Another factor significantly associated with RSB was the age at sexual debut, where students who started sex at the age of 10-17 years had higher odds of RSB. This finding is in line with a study conducted among students in Ethiopia [10], a population-based cross-sectional study conducted in Zambia among sexually active female adolescents aged 15-19 years [39], and a cross-sectional study in China among college students, where the odds of having condom-less sex at the latest sexual intercourse increased among those who reported early sexual debut [40]. A study conducted on sexual behavior among university students in China showed that those who started sex at an early age might have more sexual partners in their lifetime than those who started sex late [41].…”
Section: Discussionsupporting
confidence: 91%
“…Another factor significantly associated with RSB was the age at sexual debut, where students who started sex at the age of 10-17 years had higher odds of RSB. This finding is in line with a study conducted among students in Ethiopia [10], a population-based cross-sectional study conducted in Zambia among sexually active female adolescents aged 15-19 years [39], and a cross-sectional study in China among college students, where the odds of having condom-less sex at the latest sexual intercourse increased among those who reported early sexual debut [40]. A study conducted on sexual behavior among university students in China showed that those who started sex at an early age might have more sexual partners in their lifetime than those who started sex late [41].…”
Section: Discussionsupporting
confidence: 91%